Augmented Reality-Based Learning Media for Adzan and Iqomah in Madrasah Ibtidaiyah: Media Pembelajaran Berbasis Augmented Reality untuk Adzan dan Iqomah di Madrasah Ibtidaiyah - Ummah, Mashlahatul; Nisak, Nur Maslikhatun (Indonesian Journal of Islamic Studies, 2025)
Background: Islamic Religious Education in elementary schools often faces low student engagement due to monotonous teaching methods. Specific Background: Teachers rarely use technology-based learning media, resulting in students’ difficulty memorizing Adzan and Iqomah properly. Gap: Few studies have explored the integration of Augmented Reality (AR) for Islamic studies in Madrasah Ibtidaiyah. Aim: This research aims to develop AR-based learning media on Adzan and Iqomah material for second-grade students. Results: The AR media was developed through the ADDIE model (analysis, design, development, implementation, and evaluation) and showed improved student motivation, understanding, and memorization accuracy. Novelty: The use of AR in teaching Islamic rituals at the elementary level represents a creative approach that merges technology with religious education. Implications: The findings emphasize the importance of digital innovation to strengthen students’ engagement and teachers’ creativity in Islamic learning. Highlight & Keyword Highlights: Development of AR media for Islamic education Improved student motivation and learning engagement Integration of technology in Madrasah Ibtidaiyah learning Keywords: Augmented Reality, Learning Media, Adzan, Iqomah, Islamic Education